INFLUENCE OF MYTHONYMS ON THE FORMATION OF UZBEK FOLK PROVERBS - Safarova Zamira Rustamovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
It is known from the past that from the very beginning, humanity has formed non-existent images in its thinking because of its belief in unusual forces unknown to it, its fear of natural disasters. By the way, such images express negative and positive qualities, the term mythonyms arose in the oral speech of peoples. Mythonyms directly influence the formation of proverbs and are one of the factors denoting the worldview and way of life of the people through mythological images. This article talks about the influence of myths on the formation of Uzbek folk proverbs.